2015
DOI: 10.4025/actasciagron.v37i2.19329
|View full text |Cite
|
Sign up to set email alerts
|

<b>Diallel analysis of maize hybrids for agronomic and bromatological forage traits

Abstract: ABSTRACT. The aim of this study was to evaluate a diallel of maize hybrids for traits related to forage production and nutritional value. Six commercial hybrids were used as parents. The crosses were made according to a complete diallel design, obtaining the F1 and reciprocal crosses. The evaluations were performed in the main and second crop seasons in the 2010/2011 crop year at the Center for Technological Development in Agriculture of the Federal University of Lavras, located in Lavras, Minas Gerais State, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 11 publications
4
9
0
1
Order By: Relevance
“…This indicates that additive and non-additive genes control the traits related to silage production and its bromatological characteristics. These data corroborate the results from other studies (Ertiro et al, 2013;Guerrero et al, 2014;Mendes et al, 2015).…”
Section: Individual and Join Analyses Of Variance And Heritabilitysupporting
confidence: 93%
See 2 more Smart Citations
“…This indicates that additive and non-additive genes control the traits related to silage production and its bromatological characteristics. These data corroborate the results from other studies (Ertiro et al, 2013;Guerrero et al, 2014;Mendes et al, 2015).…”
Section: Individual and Join Analyses Of Variance And Heritabilitysupporting
confidence: 93%
“…Many studies have indicated interactions between corn genotypes and the environment for several important traits such as grain yield and bromatological quality of silage (Gralak et al, 2014;de Souza Neto et al, 2015;Marcondes et al, 2015;Mendes et al, 2015;Marcondes et al, 2016).…”
Section: Individual and Join Analyses Of Variance And Heritabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This interspecific tetraploid population presented higher additive variability than that observed in a population of diploid U. ruziziensis (Simeão et al, 2016c), or Panicum virgatum L. (Bhandari et al, 2010) or Panicum maximum (Resende et al, 2004). Most of the traits evaluated presented more addictive effect, so the selection and use of parents with higher GCA are reasonable (Mendes et al, 2015). It must be considered, however, that there was no statistically significant variability between sexual and apomictic parents for several traits (Table 2).…”
Section: Diallel Analysis and Selection Methodsmentioning
confidence: 79%
“…Maternal effects indicate that the traits had mitochondrial mode of inheritance pattern implying that when selecting parents for hybridization in soybean for bruchid resistance breeders should give female parent priority (Cai et al, 2012). The significant difference between reciprocal crosses indicated that non-chromosomal maternal effects could have contributed to a heterotic response (Mendes et al, 2015), and presence of the interaction of the genes with nuclear factors or the expression of extranuclear genes (Cai et al, 2012).…”
Section: Discussionmentioning
confidence: 99%